The Legacy of Thatcherism: Educational Inequalities and Family Capital in Ian McEwan’s Machines Like Me - Hu, Jingxuan; Liang, Xiaohui (International Journal of Education and Humanities, 2025)
In Ian McEwan's acclaimed science fiction novel Machines Like Me, most critics focus on the ethical anxieties surrounding human characters and artificial intelligence interactions. However, these studies often overlook the novel’s potential as a compelling work of BrexLit, particularly in its deep exploration of the lasting impact of Thatcherism on British social life. This includes its focus on family structures and the ethical challenges of child development, factors that contributed to the conditions leading to Brexit. The central issue explored is the generational reproduction of educational inequalities exacerbated by Thatcher’s policies. This study aims to analyze the disadvantaged position of Mark, a young boy growing up in a family facing economic hardship, fragmented social networks, and limited educational opportunities. Using Pierre Bourdieu’s three-dimensional framework of cultural capital theory—economic capital, social capital, and cultural capital—the paper examines how deficiencies in these forms of capital contribute to the reproduction of inequalities in Mark’s life. These challenges are reflected in the lives of three adult characters: Charlie, Mariam, and Miranda. The findings reveal that Mark’s psychological trauma and practical dilemmas are direct consequences of insufficient family support in terms of these three forms of capital. This highlights how Thatcher-era policies intensified educational inequalities across generations. The study underscores the need for policies that address educational disparities and strengthen family capital to mitigate the long-term effects of inequality, particularly in the post-Brexit era